Comprehensive transcriptomic analysis shows disturbed calcium homeostasis and deregulation of T lymphocyte apoptosis in inclusion body myositis - Johari Mridul; Vihola Aanna; Palmio Johanna; Jokela Manu; Jonson Per Harald; Sarparanta Jaakko; Huovinen Sanna; Savarese Marco; Hackman Peter; Udd Bjarne (Springer, 2022)
Objective: Inclusion body myositis (IBM) has an unclear molecular etiology exhibiting both characteristic inflammatory T-cell activity and rimmed-vacuolar degeneration of muscle fibers. Using in-depth gene expression and splicing studies, we aimed at understanding the different components of the molecular pathomechanisms in IBM.
Methods: We performed RNA-seq on RNA extracted from skeletal muscle biopsies of clinically and histopathologically defined IBM (n = 24), tibial muscular dystrophy (n = 6), and histopathologically normal group (n = 9). In a comprehensive transcriptomics analysis, we analyzed the differential gene expression, differential splicing and exon usage, downstream pathway analysis, and the interplay between coding and non-coding RNAs (micro RNAs and long non-coding RNAs).
Results: We observe dysregulation of genes involved in calcium homeostasis, particularly affecting the T-cell activity and regulation, causing disturbed Ca2+-induced apoptotic pathways of T cells in IBM muscles. Additionally, LCK/p56, which is an essential gene in regulating the fate of T-cell apoptosis, shows increased expression and altered splicing usage in IBM muscles.
Interpretation: Our analysis provides a novel understanding of the molecular mechanisms in IBM by showing a detailed dysregulation of genes involved in calcium homeostasis and its effect on T-cell functioning in IBM muscles. Loss of T-cell regulation is hypothesized to be involved in the consistent observation of no response to immune therapies in IBM patients. Our results show that loss of apoptotic control of cytotoxic T cells could indeed be one component of their abnormal cytolytic activity in IBM muscles.